A review of the Six Sigma belt system for manufacturing small and medium-sized enterprises. Issue 2 (3rd April 2019) - Stankalla, Roland; Chromjakova, Felicita; Koval, Oksana
Abstract: The Six Sigma methodology creates many possibilities for radically improving process and product quality. While Six Sigma was initially applied within large corporations, the interest of small and medium-sized enterprises in improvement initiatives is increasing. A decade ago, small and medium-sized enterprises became aware that they can enhance their capability, improve quality, and increase their profitability by using Six Sigma. One of the most critical success factors for the implementation of Six Sigma is a strong organizational infrastructure led by different Six Sigma belts. Thus, the aim of this article is to examine the Six Sigma belt system for small manufacturing companies based on a detailed literature review. The fact that few research papers have been published regarding this research field indicates the Six Sigma belt system for small and medium-sized enterprises has not yet been adequately studied and thus opens the door for future research. Nevertheless, it can be concluded that the original Six Sigma belt roles used by large organizations cannot simply be transferred for the application in small enterprises, as there are too many differences between these two company types. This means an extensive organizational infrastructure like in large organizations is not needed in small enterprises. There are various expert opinions but almost no empirical evidence regarding the availability, proportion to the total workforce, working time, hierarchy, project executions, and cost savings of the various Six Sigma belts in small enterprises. For this reason, this paper highlights the need for a standardized approach of the Six Sigma belt system for manufacturing small and medium-sized enterprises.